2016
DOI: 10.1136/bmjopen-2015-010524
|View full text |Cite
|
Sign up to set email alerts
|

Is self-monitoring of blood glucose effective in improving glycaemic control in type 2 diabetes without insulin treatment: a meta-analysis of randomised controlled trials

Abstract: ObjectiveThe present study aimed to verify the effectiveness of self-monitoring of blood glucose (SMBG) in patients with non-insulin-treated type 2 diabetes (T2D).MethodsA comprehensive literature search was conducted in PubMed, Cochrane Library, Web of Science, ScienceDirect and ClinicalTrials.gov from their respective inception dates to 26 October 2015. Eligible randomised controlled trials (RCTs) were included according to prespecified criteria. The quality of the included RCTs was evaluated according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 29 publications
2
66
1
3
Order By: Relevance
“…Within primary care, POCT have been incorporated into chronic disease self-management programs to improve glycemic control in type-2 diabetes mellitus and therapeutic anticoagulation for those on warfarin (Heneghan et al, 2016, Zhu et al, 2016). However, its role in promoting guideline-recommended CVD preventive therapies among an asymptomatic, but at-risk, general population is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Within primary care, POCT have been incorporated into chronic disease self-management programs to improve glycemic control in type-2 diabetes mellitus and therapeutic anticoagulation for those on warfarin (Heneghan et al, 2016, Zhu et al, 2016). However, its role in promoting guideline-recommended CVD preventive therapies among an asymptomatic, but at-risk, general population is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis was carried out on sample size, which is a dominant factor determining the robustness of the results. The meta‐analysis was thus repeated after excluding studies with sample size less than 100 . All analyses were performed using Review Manager (RevMan) 5.3 software.…”
Section: Methodsmentioning
confidence: 99%
“…Several systematic reviews and meta‐analyses have explored the effects of SMBG on glycaemic control in non‐insulin‐treated T2D patients, showing a reduction of glycated haemoglobin A1c (HbA1c) from 0.21% to 0.34% and a slight improvement in body mass index (BMI) . Despite the improvement in glycaemic control and BMI, finger pricking‐associated pain remains a burden of diabetes management .…”
Section: Introductionmentioning
confidence: 99%
“…It reflects in a much better way intra-and interday glycemic excursions that may lead to acute events (such as hypoglycemia) or postprandial hyperglycemia, which have been linked to both microvascular and macrovascular complications (28). Additionally and beyond the effects of the meta-analysis of Zhu et al (29), Rodbard (30) reported that CGM has been demonstrated to be useful in reducing the risks of hypo-and hyperglycemia too, improving glycemic variability and increasing patients' quality of life in both type 1 and type 2 diabetes (30). Additionally and beyond the effects of the meta-analysis of Zhu et al (29), Rodbard (30) reported that CGM has been demonstrated to be useful in reducing the risks of hypo-and hyperglycemia too, improving glycemic variability and increasing patients' quality of life in both type 1 and type 2 diabetes (30).…”
Section: Glucose Monitoringmentioning
confidence: 99%